Effectiveness of Quantum Learning for Teaching Linear Program at the Muhammadiyah Senior High School of Purwokerto in Central Java, Indonesia - Kusno, Kusno; Purwanto, Joko (EDUCARE, 2011)
ABSTRACT: For most Indonesian students, Mathematics is still regarded as a difficult and scaring subject compared to other subjects. Therefore, there should be a learning strategy which can empower all the available potential to achieve the learning objectives as a whole. In relation to the learning process of Mathematics, the choice of learning strategy is also based on the achievement of the learning objectives. One way of realizing that is through the use of quantum learning. The aim of this research is: (1) to find out the effectiveness of quantum learning for teaching mathematics; and (2) to analyze the difference the result of quantum learning and that of the conventional one. Two classes of grade X were randomly taken as sample out of five available, one class being the experimental group and the other control. This random sampling was due to the fact that students are distributed evenly on ability basis. Data was taken using test and non-test techniques (observation and questionnaire). To find out the effectiveness of this quantum learning, descriptive analysis was used toward: (1) studentâs activity during the learning process; (2) the teacherâs ability in managing the learning process; (3) studentâs response toward the learning model; and (4) the studentâs mastery. While ANAKOVA inferential analysis was used to test the difference on the learning achievement. The result of the two analysis were that quantum learning was effective and there was significant difference in which the quantum learning gave a better learning achievement than the conventional one. KEY WORDS: Teaching and learning effectiveness, Mathematics subject, quantum learning concept, and modern and conventional learning.Â Â About the Authors: Kusno, M.Pd. and Joko Purwanto, M.Si. are Lecturers at the Department of Mathematics Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, PO Box 202, Purwokerto 53182, Central Java, Indonesia. They can be reached at: pakusno@yahoo.com and jokotien@gmail.comHow to cite this article? Kusno & Joko Purwanto. (2011). âEffectiveness of Quantum Learning for Teaching Linear Program at the Muhammadiyah Senior High School of Purwokerto in Central Java, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.83-92. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 30, 2011); Revised (July 30, 2011); and Published (August 17, 2011).